BIOFILM FORMATION AT THE BACTERIAL VAGINOSIS - E. S. Berezovskaya; I. O. Makarov; M. A. Gomberg; E. I. Borovkova; E. A. Chulkova; L. A. Arakelyan (Акушерство, гинекология и репродукция, 2016)
A review of the literature dedicated to the state of knowledge of the problem of recurrent bacterial vaginosis, presents the modern theory of pathogenesis in terms of formation of microbial biofilms and Association of microorganisms.